An iodine-containing diluted magnetic semiconductor (Zn 90% ,Cr 10% )Te:N thin film material and preparation method thereof
By co-doping nitrogen (N) and iodine (I) in dilute magnetic semiconductor (Zn90%, Cr10%) Te, adjusting the distance and binding energy between Cr atoms solves the problem that existing materials cannot exhibit ferromagnetic properties at 2K temperature. problem, achieving a combination of high ferromagnetic Curie temperature and strong magnetic properties, which is suitable for applications in photon spin detection diodes and 2-dimensional electronic devices.
Patent Information
- Application Number
- CN202210771209.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-06-30
- Publication Date
- 2025-01-24
- Estimated Expiration
- 2042-06-30
AI Technical Summary
The existing dilute magnetic semiconductor (Zn,Cr)Te materials are difficult to control carrier movement through external voltages, and cannot exhibit ferromagnetic characteristics at 2K temperatures, which limits their use in devices such as optical spin detectors and spin-MOSFETs. application.
By mixing nitrogen (N) and iodine (i) at the CCP (N) and iodine (i) of Rare Magnetic Semiconductor (ZN90%, CR10%) TE, the distance and combination of CR atoms enhance the dual -exchange interaction of CR 3D electronics and P electrons. Improve the temperature of the material of the material, so that it presents the iron magnetic characteristics above 2K.
Achieve the iron magnetic characteristics of the material at a temperature above 2K, improve the temperature of the iron magnetic residence to 20K, enhance the magnetic properties of the material, and maintain its semiconductor characteristics. Essence
Smart Images

Figure CN115148445B_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the field of preparation of p-type diluted magnetic semiconductors, and specifically relates to an iodine-containing diluted magnetic semiconductor (Zn 90% %,Cr 10% )Te:N thin film material and preparation method thereof. Background Art
[0002] In today's society, with the booming development of the Internet, the exchange capacity and speed of information are getting faster and faster, which requires higher and higher performance of hardware based on data exchange, and further development of electronic engineering. For example, the minimum line width of semiconductor transistors based on Si has been reduced to 5nm, and the development of other optoelectronic devices is also changing with each passing day. These use the carriers in semiconductors to conduct information and process operations. On the other hand, the media for recording and saving information, such as hard disk drives (HDDs), use the electron spin of magnetic bodies to store and process information. With the discovery of giant magnetoresistance effect and tunnel magnetoresistance effect, most researchers believe that the freedom of both the electron spin and charge movement of magnetic bodies can be used to store, transmit and calculate information.
[0003] Based on the above, most of the research objects are semiconductors, metals and insulators. Since it is easy to realize the movement of charges and the control of photoelectrons in semiconductors, adding magnetic elements to semiconductors has become an important research object, which is called diluted magnetic semiconductors (DMS). In the study of DMS, the research objects are the combination of different elemental substances, the growth of materials, and the processing technology of microscale structures.
[0004] Among the many DMS material studies, based on III-V compound semiconductors, such as InAs and GaAs semiconductors, after replacing part of the III group elements and Mn elements, (In, Mn) As and (Ga, Mn) As materials can exhibit ferromagnetic properties. Based on II-VI compound semiconductors, such as ZnSe and ZnTe, after replacing part of the Zn elements and Cr elements, (Zn, Cr) Se and (Zn, Cr) Te can exhibit ferromagnetic properties. In addition, in order to achieve the control of charge, it is necessary to dope the above materials to obtain p-type or n-type rare-earth magnetic semiconductors. For example, in n-type (Zn, Cr) Te semiconductors, donor impurity elements generally include Cl, Al, I and other elements. For p-type (Zn, Cr) Te semiconductors, acceptor impurity elements generally include N, As, P and other elements. There are two doping methods: MBE method and MOCVD growth method. Regardless of whether the MBE or MOCVD growth method is used, during the heating growth process of the metal / metal compound, various elements will form Zn-Zn bonding, Te-Te bonding, bonding between donor impurities, etc. due to the problem of covalent binding energy during thermal equilibrium, resulting in the precipitation of magnetic elements in local areas of the semiconductor material, thereby losing the characteristics of the semiconductor itself and showing the characteristics of the metal.
[0005] (Zn, Cr)Te is an insulator. It is difficult to control the movement of carriers in the material by external voltage. Therefore, it is impossible to use this material to make devices such as optical spin detectors and spin-MOSFET. Under this premise, it is necessary to dope this material to form a p-type or n-type semiconductor in order to control the charge. Ozaki et al. (Suppression of ferromagnetism due to hole doping in Zn1-xCrxTe grown by molecular-beamepitaxy[J].Applied Physics Letters,2005,87(19):1488.) used N atoms as the acceptor material and added them into (Zn, Cr)Te. They found that when the concentration of N atoms reached 10 19 ~10 20 cm -3 Finally, even when the Cr concentration in (Zn, Cr)Te:N is 10%, the material does not exhibit ferromagnetic properties.
[0006] The inventors believe that the addition of N atoms changes the state of the outermost 3d electrons of Cr, resulting in a larger binding energy between Cr atoms, causing the Cr atoms to move away from each other under the action of repulsive force, reducing the probability of metastable decomposition of Cr atoms and weakening the double interaction between Cr-Te-Cr, thus causing the material to be unable to exhibit ferromagnetic properties at a temperature of 2K. Summary of the invention
[0007] In view of the above problems, the present invention provides an iodine-containing diluted magnetic semiconductor (Zn 90% ,Cr 10% )Te:N thin film material and preparation method thereof.
[0008] The inventors found that in iodine-containing diluted magnetic semiconductors (Zn 90% ,Cr 10% )In the Te:N film, the material will exhibit ferromagnetic properties only when the distance between Cr atoms is in an appropriate range.
[0009] The present invention is a p-type semiconductor material. By co-doping nitrogen and iodine into a rare-earth magnetic semiconductor film and controlling the doping concentration ratio of N and I to change the number of electrons in the Cr 3d orbit, the metastable decomposition probability of Cr atoms can be enhanced, and the distance between adjacent Cr atoms can be made closer, so the ferromagnetic Curie temperature can be increased.
[0010] Specifically, the present invention adjusts the molecular line intensity ratio of various elements and controls the covalent binding energy between various elements, especially magnetic elements and other elements through a low-temperature annealing treatment method. In a thermal equilibrium state, the distribution of magnetic atoms Cr in the material is adjusted to enhance the double exchange interaction between 3d electrons and p electrons of Cr, thereby increasing the ferromagnetic Curie temperature of the material to make its Curie temperature greater than or equal to 2K, thereby obtaining a high-quality magnetic semiconductor film.
[0011] The thin film material prepared by the present invention can control the movement of carriers (holes) by using the change of external current / voltage, and can be applied to the manufacture of photon spin detection diodes (spin-DIODE) or two-dimensional electronic devices with heterojunction structures.
[0012] The present invention provides an iodine-containing diluted magnetic semiconductor (Zn 90% ,Cr 10% ) A method for preparing a Te:N thin film material, comprising the following contents:
[0013] Step 1: Pre-growth treatment of the semi-insulating GaAs substrate
[0014] As in the few atomic layers on the surface of the GaAs substrate can easily react chemically with oxygen in the air to form an As oxide film with a thickness of several nm. In addition, organic particles floating in the air can easily adhere to the surface during transportation and unsealing. These oxides, organic or inorganic particle pollutants can seriously affect the properties of the semiconductor, such as destroying the high resistance state of the substrate. Therefore, it is necessary to treat these substances. The present invention uses sulfuric acid, hydrochloric acid, and hydrogen peroxide to soak and clean the GaAs substrate;
[0015] Furthermore, the volume ratio of sulfuric acid: hydrochloric acid: hydrogen peroxide is 4:1:1, and stirring is performed at the same time, and the soaking, stirring and cleaning time is 5 minutes. Finally, anhydrous ethanol is used for cleaning and dehydration.
[0016] Step 2: Treating GaAs surface defects using molecular beam epitaxy
[0017] After pre-treatment, oxides are still present on the surface of the GaAs substrate, and damage and lattice defects are inevitably present on the surface of the GaAs substrate.
[0018] For the oxide on the surface of the substrate, the present invention removes the oxide film on the surface by heating the temperature in the range of 500-600°C and maintaining it for 4-6 minutes. The oxide can be completely evaporated from the surface of the substrate within this time and temperature range to achieve the removal effect.
[0019] Furthermore, in a specific embodiment of the present invention, the heating temperature of the GaAs substrate is 560° C. and the holding time is 5 minutes.
[0020] During the heating process of the GaAs substrate, especially when the temperature exceeds 400°C, As atoms will evaporate from the surface, causing lattice defects on the substrate surface. At this time, the As atoms need to be compensated.
[0021] In view of the lattice defects on the substrate surface, the present invention uses molecular beam epitaxy technology to compensate As atoms. The compensation method is to evaporate one of Te atoms, Se atoms and As atoms onto the substrate surface, thereby achieving the purpose of lattice defect repair.
[0022] In a specific embodiment of the present invention, a Te atom source is used to compensate As atoms. If As atoms are used for compensation, within this temperature range, Ga and As atoms from the As evaporation source will undergo secondary decomposition after combining. However, the binding energy of Ga-Te is greater than that of Ga-As, which reduces the probability of secondary decomposition after combining, so it is preferred that Te atoms compensate the substrate surface.
[0023] Furthermore, in the specific technical solution of the present invention, when Te atoms are used to compensate the substrate surface, the molecular line intensity of Te atoms is 5x10 -8 Torr.
[0024] Through the above steps, the organic or inorganic pollutants on the substrate are thoroughly cleaned, thereby ensuring the high resistance state of the GaAs substrate.
[0025] "Molecular beam epitaxy" is a new technology for growing high-quality crystal thin films on crystal substrates. Under ultra-high vacuum conditions, the vapor generated by heating a furnace filled with various required components is collimated by a small hole to form a molecular beam or atomic beam, which is directly sprayed onto a single crystal substrate at an appropriate temperature. At the same time, the molecular beam is controlled to scan the substrate, so that molecules or atoms can be "grown" layer by layer on the substrate according to the crystal arrangement to form a thin film.
[0026] Step 3: Growth of ZnTe buffer layer
[0027] The lattice constant of GaAs is Nitrogen (Zn 90% ,Cr 10% )The lattice constant of Te:I film is There is a 7% mismatch in the lattice constant. 90% ,Cr 10% )Te:I thin film, a ZnTe buffer layer needs to be grown on the GaAs substrate.
[0028] In the technical solution of the present invention, the specific method of growing the ZnTe buffer layer is as follows: when the growth temperature is in the range of 280-320°C, Zn atoms and Te atoms can form a ZnTe compound semiconductor. When the temperature is outside the range of 280-320°C, a Zn-Zn region and a Te-Te region are formed, showing metallic properties.
[0029] In the technical solution of the present invention, the optimal growth temperature is 300°C. Under this temperature condition, the molecular line intensity ratio of Zn / Te is adjusted to 1:1.5. After the film is grown for 1 hour, the lattice constant of the ZnTe buffer layer can reach The lattice constant of the (Zn,Cr)Te:I film is close to that of the ZnTe layer, thus ensuring that the nitrogen-containing (Zn 90% ,Cr 10% )High-quality growth of Te:I thin films.
[0030] Further, the ZnTe buffer layer has a thickness of 50 to 400 nm;
[0031] Further, the thickness of the ZnTe buffer layer is 340-380 nm;
[0032] Furthermore, the thickness of the ZnTe buffer layer is 360 nm.
[0033] Step 4: Iodine (Zn 90% ,Cr 10% ) Growth of Te:N thin film
[0034] Contains iodine (Zn 90% ,Cr10% When the (Zn,Cr)Te:N thin film layer is grown, the molecular line intensity ratio of Zn:Te is 1.5 to 2.4:1 in the MBE growth chamber. Specifically, in the technical solution of the present invention, the molecular line intensity ratio of Zn:Te is 2:1. Under this ratio, it is beneficial for N atoms and Zn atoms to form covalent bonds, reducing the probability of empty sites of Zn atoms in the (Zn,Cr)Te:N compound.
[0035] Furthermore, in the technical solution of the present invention, the total vapor pressure of Zn atoms and Te atoms is 6x10 -7 Torr.
[0036] In the technical solution of the present invention, the vapor pressure of Cr atoms is 4 to 8×10 -8 Torr.
[0037] Furthermore, the vapor pressure of Cr atoms is 8×10 -8 Torr.
[0038] Semiconductor ZnTe is an insulator because the Fermi level is formed in the middle of the semiconductor band gap energy level. By replacing Te atoms with N atoms, the Fermi level can be lowered to near the valence band and converted into a p-type semiconductor. Therefore, the present invention uses N elements to dope the film to convert ZnTe into a nitrogen-doped ZnTe:N p-type semiconductor.
[0039] The present invention needs to dope iodine atoms during the material growth process, the purpose of which is to change the number of electrons in the 3d orbit of the Cr atoms, so that the binding energy between the Cr atoms is reduced, so that the Cr atoms form a Cr-Te-Cr or Cr-N-Te blende structure under the action of attraction, enhance the double exchange interaction between Cr 3d electrons and Te p electrons, reduce the probability of forming a CrTe hexagonal unit cell structure, and make the ferromagnetic Curie temperature Tc of the material ≥2K, which can eventually reach 20K.
[0040] In the technical solution of the present invention, N atom doping is carried out by ion implantation, and the doping concentration of N atoms is 10 19 ~10 20 cm -3 Heat the CdI2 compound to 180℃~220℃ and control the iodine atom doping concentration to 10 18 ~10 19 cm -3 ; The doping concentration ratio of N atoms and I atoms is 1:1 to 10:1
[0041] In a specific embodiment of the present invention, the doping concentration of N atoms is controlled to be 10 20 cm -3 .
[0042] In the technical solution of the present invention, the iodine atom doping method is to heat the CdI2 compound to 180°C to 220°C, so that the I atoms are separated from the CdI2 compound and doped into the film as donor impurities. The doping concentration of the I atoms increases with the increase of the CdI2 heating temperature.
[0043] In a specific embodiment of the present invention, the doping concentration of I atoms is controlled to be 10 19 cm -3 .
[0044] The present invention controls the growth rate of the film to 0.1 nm / s through the vapor pressure ratio of each element.
[0045] In the technical solution of the present invention, the iodine-containing (Zn 90 ,Cr 10% )The growth temperature of Te:N thin film layer is 270~330℃.
[0046] Furthermore, iodine-containing (Zn 90 ,Cr 10% )The growth temperature of Te:N thin film layer is 300℃.
[0047] In the technical solution of the present invention, iodine (Zn 90 ,Cr 10% )The thickness of the Te:N thin film layer is 50~720nm.
[0048] Furthermore, iodine-containing (Zn 90 ,Cr 10% ) The thickness of the Te:N thin film layer is 50 to 360 nm;
[0049] Furthermore, iodine-containing (Zn 90 ,Cr 10% )The thickness of the Te:N thin film layer is 360nm.
[0050] Step 5: Iodine (Zn 90% ,Cr 10% ) Low temperature annealing of Te:N thin film materials
[0051] The atomic radius of N as an acceptor element is approximately The atomic radius of the replaced element Te is approximately And the lattice constant of ZnTe is Therefore, N atoms have a certain probability of existing in the lattice gaps of ZnTe, thus destroying the blende structure of ZnTe.
[0052] The annealing treatment proposed in the present invention can increase the probability of N atoms occupying Te atomic lattice points and reduce the probability of N atoms occupying ZnTe lattice vacancies. In addition, the binding energy between Cr atoms can be further increased, so that a part of the crystal region can form a Cr-Te-Cr or Cr-N-Te sphalerite structure, and the material exhibits ferromagnetic properties, thereby obtaining high-quality iodine-containing (Zn) sphalerite with a sphalerite structure. 90% , Cr10%)Te:N crystal film. In the technical solution of the present invention, the annealing temperature is 350-450°C and the heat preservation time is 8-12 minutes.
[0053] Furthermore, in a specific embodiment of the present invention, the annealing temperature is 400° C. and the holding time is 10 min.
[0054] The present invention also aims to provide an iodine-containing rare earth magnetic semiconductor (Zn 90% ,Cr 10% )Te:N thin film material, the concentration ratio between nitrogen and iodine in the material is 1:1 to 10:1, and the ferromagnetic Curie temperature of the material is 2K to 20K;
[0055] Furthermore, the hole concentration of the thin film material is 5×10 19 cm -3 ~5×10 20 cm -3 , containing iodine-containing magnetic semiconductors (Zn 90% ,Cr 10% ) The resistivity of Te:N thin film material is 0.5Ω·cm~1.5Ω·cm;
[0056] Furthermore, the hole concentration of the thin film material is 10 20 cm -3 , containing iodine-containing magnetic semiconductors (Zn 90% ,Cr 10% )The resistivity of Te:N thin film material is 1Ω·cm.
[0057] The beneficial effects of the present invention are:
[0058] 1. In the iodine-containing rare-earth magnetic semiconductor (Zn 90% ,Cr 10%)Te:N thin film material is prepared by co-doping N atoms with I atoms, and the doping concentration ratio of N atoms and I atoms is controlled in the range of 1:1 to 10:1, which reduces the binding energy between Cr atoms. Under the action of gravity, Cr atoms form a blende structure of Cr-Te-Cr, which improves the double exchange interaction between Cr 3d electrons and p electrons without destroying the crystal structure. Compared with the N-doped (Zn, Cr)Te material grown by Ozaki et al., the ferromagnetic and semiconductor properties of the material are retained, and a p-type semiconductor is prepared.
[0059] 2. The iodine-containing diluted magnetic semiconductor (Zn 90% ,Cr 10% )The ferromagnetic Curie temperature of the Te:N thin film material is 20 K. Compared with the material grown by Ozaki et al., the ferromagnetic Curie temperature is higher.
[0060] 3. Using molecular beam epitaxy, crystal growth can be carried out at low temperatures, and thin film growth at the atomic level can be achieved with a growth rate of 0.1nm / s.
[0061] 4. I is an n-type semiconductor doping element, and N is a p-type semiconductor doping element. The present invention controls the type and concentration of carriers in the thin film material by co-doping I atoms and N atoms, and provides a new method for introducing carriers into a semiconductor (Zn, Cr)Te thin film material.
[0062] Instruction Manual
[0063] Figure 1 In order to prepare iodine-containing diluted magnetic semiconductor (Zn 90% ,Cr 10% ) Schematic diagram of Te:N film. In the figure, 1 represents the growth chamber of MBE, 2 represents the Te atomic source, 3 represents the Cr atomic source, 4 represents the N atomic source, 5 represents the Zn atomic source, 6 represents the CdI2 evaporation source, and 7 represents the film growth position, which is located in the center of the growth chamber.
[0064] Figure 2 This is a schematic side cross-sectional view of a semi-insulating GaAs substrate.
[0065] Figure 3 is a schematic side cross-sectional view of growing a ZnTe buffer layer on a GaAs substrate, where 1 indicates that the thickness of the ZnTe buffer layer is 360 nm;
[0066] Figure 4 In order to grow iodine-containing (Zn 90% ,Cr 10% )Te:N thin film material side cross-sectional diagram, Figure 1 represents iodine (Zn 90% ,Cr10% )The thickness of the Te:N thin film layer is 360nm.
[0067] Figure 5 To test the iodine (Zn 90% ,Cr 10% )Magnetic characteristic curves obtained for Te:N thin film material.
[0068] Figure 6 Iodine (Zn 90% ,Cr 10% )Arrot Plot fitting curve of Te:N thin film material at different temperatures.
[0069] Figure 7 This is the RHEED image of the GaAs surface.
[0070] Figure 8 RHEED images of ZnTe buffer layer films of different thicknesses grown on treated GaAs substrates.
[0071] Fig. 9 RHEED images of ZnTe buffer layer films at different growth temperatures.
[0072] Fig.10 The iodine content (Zn 90% ,Cr 10% ) RHEED image of Te:N thin film material.
[0073] Fig.11 The iodine (Zn 90% ,Cr 10% ) RHEED image of Te:N thin film material.
[0074] Fig.12 Iodine (Zn 90% ,Cr 10% ) Relationship diagram of ferromagnetic Curie temperature of Te:N thin film material at different N atom to I atom doping concentration ratios.
[0075] Fig.13 The iodine-containing (Zn) 90% ,Cr 10% )X-ray refraction curve of Te:N thin film material.
[0076] Fig.14 The iodine-containing (Zn) 90% ,Cr 10% )X-ray reflection curve diagram of Te:N thin film material. DETAILED DESCRIPTION
[0077] In order to make the purpose, technical solution and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with the accompanying drawings and embodiments. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not used to limit the present invention.
[0078] Any feature disclosed in this specification (including any additional claims, abstract and drawings), unless otherwise stated, may be replaced by other equivalent or alternative features with similar purposes. That is, unless otherwise stated, each feature is only an example of a series of equivalent or similar features.
[0079] In the present invention, RHEED is an abbreviation for reflected high-speed electron back-electron eddy current. RHEED is usually used to track the crystal state of the film growth during molecular beam epitaxy. When the RHEED image reflects the arrangement of atoms within a few nm on the film surface, when the image is in the form of bands / dots and lines, it indicates that the film surface is in a single crystal state. When the image is in the form of rings, dots, or even no image, it indicates that the film surface is in a polycrystalline state or is uneven, and the crystal quality is very low.
[0080] Example 1
[0081] Step 1: Pre-growth treatment of the semi-insulating GaAs substrate
[0082] The present invention uses sulfuric acid: hydrochloric acid: hydrogen peroxide = 4:1:1 ratio to soak and clean the GaAs substrate, stirring it at the same time, and the soaking and stirring cleaning time is 5 minutes. Finally, 99% anhydrous ethanol is used for cleaning and dehydration.
[0083] Step 2: Use molecular beam epitaxy to grow GaAs( Figure 2 ) Surface defects are treated
[0084] The specific method is to heat the GaAs substrate to 560°C and keep it for 5 minutes. Under this condition, the oxide can be completely removed. However, during the heating process of the GaAs substrate, especially when the temperature exceeds 400°C, As atoms will evaporate from the surface, causing lattice defects on the substrate surface, and it is necessary to compensate for the As atoms. The specific method of the present invention uses a Te atomic source to compensate for the As atoms, such as Figure 1 As shown, the Te atom source is heated to control the vacuum vapor pressure (molecular line intensity) of Te atoms to 5x10 -8 Torr.
[0085] Step 3: Growth of ZnTe buffer layer (Buffer) Figure 3 )
[0086] The lattice constant mismatch rate of GaAs and (Zn, Cr)Te:N reaches 7%, so it is necessary to grow a ZnTe buffer layer. The specific method is to set the substrate temperature to 300℃, heat the Zn atomic source and the Te atomic source, so that the molecular line intensity ratio of Te / Zn reaches 1.5:1, and the molecular line intensity is 6x10 -7 Torr and 4x10 -7 Torr. Under this condition, the growth rate of compound crystallization is 0.1nm / s, and the thickness of the growth buffer layer is 360nm. After 1 hour of crystal growth, the lattice constant of ZnTe can reach The lattice constant of the ZnTe layer is close to that of the (Zn, Cr)Te:N film, thereby ensuring high-quality growth of the (Zn, Cr)Te:N film on the ZnTe layer.
[0087] Step 4: Iodine (Zn 90% ,Cr 10% )Te:N thin film growth ( Figure 4 )
[0088] The Zn, Cr and Te atomic sources were heated to make the molecular line intensity ratio of Zn:Cr:Te reach 5:1:2.5, and the molecular line intensities were 4x10 -7 Torr, 8x10 -8 Torr and 2x10 -7 Torr, at this ratio, the Cr content can be obtained to be 10%. N atom doping adopts radio frequency discharge ion implantation, the radio frequency discharge frequency is 13.56MHz, the discharge power is 100-200W, and the N2 flow rate is controlled at 0.1-1CC / min. The I atom doping element is the compound CdI2, and the heating temperature is 180-220℃. By changing the doping conditions of N atoms and I atoms, a series of materials with different N / I concentration ratios can be obtained, and the N / I concentration ratio ranges from 1 to 100.
[0089] In the present invention (Zn 90% ,Cr 10% )Te: N thin film layer growth temperature 300 ℃, growth time 1 hour, the film growth process needs to rotate the substrate, the speed is 18 ° / second, the growth of iodine (Zn 90% ,Cr 10% )The thickness of the Te:N film is 360nm.
[0090] Step 5: Iodine (Zn 90% ,Cr 10% ) Low temperature annealing of Te:N thin film materials
[0091] Treatment conditions: The film temperature is raised to 400°C and maintained for 10 minutes. This method can further improve the bonding of Cr atoms and anions in some areas, improve the bonding of N atoms in iodine-containing (Zn 90% ,Cr 10% ) distribution in the Te:N film, so that the film maintains the blende structure.
[0092] Figure 5 To test the iodine (Zn 90% ,Cr 10% ) A magnetic characteristic curve of a Te:N film (Example 1), wherein the doping concentration N / I of N atoms to I atoms is 10:1. The ferromagnetic characteristic curves of the film at different temperatures according to the change of the magnetic field are observed through the curve, and an obvious ferromagnetic characteristic curve can be seen at a temperature of 2K.
[0093] Figure 6 The Arrot Plot fitting curves at different temperatures are shown in Table 1. 90% ,Cr 10% )Te:N film (Example 1) has a ferromagnetic Curie temperature of 20 K. The iodine-containing (Zn 90% ,Cr 10% )Te:N material does not show ferromagnetic properties at 20K. This shows that the material performance of the present invention is better than that of (Zn 90% ,Cr 10% )Te:N semiconductor material.
[0094] The Hall test results show that the carriers of the film are holes, and the hole concentration can reach 10 20 cm -3 , containing iodine-containing magnetic semiconductors (Zn 90% ,Cr 10% )The resistivity of Te:N thin film material is 1Ω·cm.
[0095] Test method: When the carriers in the semiconductor thin film material move in an external magnetic field, the movement trajectory is deflected due to the influence of the Lorentz force, and a potential difference is generated at both ends of the material. In this way, it can be concluded whether the carriers in the material are holes or electrons, and the resistivity and concentration of the carriers can be obtained by calculation. It has a wide range of applications in the field of semiconductor material research.
[0096] Test equipment: British OXFORD brand.
[0097] Example 2
[0098] RHEED images of ZnTe buffer films of different thicknesses grown on treated GaAs substrates are shown in Figure 2. Figure 8 As shown. The fixed growth temperature is 300°C. When the film thickness is 50nm or 150nm, there are both dot-line images. When the film thickness is 360nm, the linear pattern is most obvious, and when the thickness is 400nm, the image shows a dot-line trend. The optimal thickness of the ZnTe buffer layer of the present invention is 360nm.
[0099] Example 3
[0100] RHEED images of ZnTe buffer layer films at different growth temperatures are shown in Figure 2. Fig. 9 As shown. The fixed film thickness is 360nm. It can be seen from the figure that when the growth temperature is 280℃, it basically presents a linear pattern, and the dot pattern is not obvious. When the growth temperature is 300℃, a very clear linear pattern is presented. When the growth temperature is 320℃, it basically presents a linear pattern, and there are also dot patterns. Therefore, the optimal growth temperature of the ZnTe buffer layer proposed by the present invention is 300℃.
[0101] Example 4
[0102] Fig.10 The iodine content (Zn 90% ,Cr 10% ) RHEED image of Te:N film. The film growth temperature is 300℃. When the film thickness is 50nm, the film shows a slight dotted pattern. As the thickness increases, the dotted pattern gradually becomes clearer. At 360nm, the dotted pattern is the clearest. When it increases to 720nm, the dotted pattern is basically unobservable, which means that the crystallinity quality of the film is very poor at this thickness.
[0103] Example 5
[0104] Fig.11 The iodine (Zn 90% ,Cr 10% ) RHEED image of Te:N film. The thickness of the film is fixed at 360nm, and the growth temperature range is 270℃~330℃. By comparing the RHEED images, it can be seen that at the growth temperature of 300℃, the RHEED image of the film is the clearest, which can indicate that the optimal growth temperature of the film is 300℃.
[0105] Comparative Example 1
[0106] like Figure 7The image shown is the RHEED image of the GaAs surface. The left image is an image without using Te atoms to compensate As atoms. The image shows a dotted pattern, which means that As atoms detach from the GaAs substrate after exceeding 400°C, and Ga atoms remain on the surface, resulting in an uneven substrate surface. The right image is an image after using Te atoms for compensation. The image shows a linear pattern, which indicates that Te atoms combine with the remaining Ga atoms to fill the vacancies left by the As atoms, thereby improving the flatness of the GaAs substrate surface to avoid the unevenness of the ZnTe buffer layer grown on it, thereby improving the crystallization quality of the multilayer film.
[0107] Comparative Example 2
[0108] Fig.12 The figure is a relationship diagram of ferromagnetic Curie temperature under different ratios of N atom to I atom doping concentration. It can be seen from the figure that when the ratio of N atom to I atom doping concentration exceeds 10 to 20 times, the ferromagnetic properties of the material disappear at 2K, which means that the material no longer has ferromagnetic properties. If ferromagnetic properties are to be exhibited, the content ratio of I atoms needs to be increased. However, since I atoms are an n-type doped material, when the ratio of N atoms to I atoms is lower than 1:1, the material will change from p-type to n-type conduction properties. Therefore, the inventor believes that in (Zn 90% ,Cr 10% )In Te:N materials, in order to maintain both ferromagnetic properties and p-type semiconductor conduction properties, the ratio of N atoms to I atoms must be higher than 1:1 and lower than 10:1.
[0109] Comparative Example 3
[0110] Fig.13 To investigate the iodine-free (Zn 90% ,Cr 10% )Te:N thin film X-ray refraction curve. The X-ray refraction curve shows that (Zn 90% ,Cr 10% ) The first maximum peak of the (004) face of the Te:N film is 60.66°, with an intensity of 125,000, which is close to the angle of the (004) face of the ZnTe semiconductor of 60.653° (theoretical value). The second maximum peak angle is 60.81°, with an intensity of 77,000. The intensity ratio of the first maximum peak to the second maximum peak is 1.62. The half-amplitude of the entire curve is 0.27°.
[0111] Fig.14 The iodine-containing (Zn) 90% ,Cr 10%)Te:N film X-ray refraction curve. There are iodine-containing (Zn 90% ,Cr 10% ) The first maximum peak of the (004) face of the Te:N film is 60.66°, with an intensity of 55,000, which is close to the angle of the (004) face of the ZnTe semiconductor, which is 60.653° (theoretical value). The second maximum peak angle is 60.81°, with an intensity of 32,000. The intensity ratio of the first maximum peak to the second maximum peak is 1.71. The half-amplitude of the entire curve is 0.26°.
[0112] By comparison Fig.13 and Fig.14 , using the iodine-containing (Zn 90% ,Cr 10% )Te:N film, the half-amplitude of the X-ray refraction curve decreased by 0.01°, and the intensity ratio of the first refraction to the second refraction peak in the curve increased by 0.09, indicating that the iodine-containing (Zn) 90% ,Cr 10% )The crystallization of Te:N film is better than that of the sample made by Ozaki et al.
[0113] The above contents are further detailed descriptions of the present invention in combination with specific implementation methods, and it cannot be determined that the specific implementation methods of the present invention are limited to these descriptions. For ordinary technicians in the technical field to which the present invention belongs, several deductions or substitutions can be made without departing from the concept of the present invention, which should be regarded as falling within the scope of protection of the present invention.
Claims
1. An iodine-containing diluted magnetic semiconductor (Zn 90% ,Cr 10% ) A method for preparing a Te:N thin film material, comprising the following contents: The semi-insulating GaAs substrate is treated before growth: the GaAs substrate is soaked and cleaned with sulfuric acid: hydrochloric acid: hydrogen peroxide in a ratio of 4:1:1, and then cleaned and dehydrated with anhydrous ethanol; Use molecular beam epitaxy technology to treat GaAs surface defects: heat the GaAs substrate to 500-600 °C, maintain for 4-6 minutes, remove the surface oxide, and then use molecular epitaxy technology to treat the GaAs substrate surface defects; when using molecular epitaxy technology to treat the GaAs substrate surface defects, the atoms used are one or more of As atoms, Te atoms, and Se atoms; Growth of ZnTe buffer layer: The ZnTe buffer layer was grown on the GaAs substrate using molecular beam epitaxy technology. The growth temperature of the ZnTe buffer layer was 300°C. The Zn atomic source and the Te atomic source were heated to make the molecular line intensity ratio of Te / Zn reach 1.5:1, and the molecular line intensities were 6x10 -7 Torr and 4x10 -7 Torr; under this condition, the growth rate of the compound crystal is 0.1nm / s, and the thickness of the growth buffer layer is 360nm; Contains iodine (Zn 90% ,Cr 10% ) Growth of Te:N thin film layer: Heat the Zn atomic source, Cr atomic source and Te atomic source to make the molecular line intensity ratio of Zn:Cr:Te reach 5:1:2.5, and the molecular line intensity is 4x10 -7 Torr, 8x10 -8 Torr and 2x10 - 7 Torr, under this ratio, the Cr content is 10%; N atom doping adopts radio frequency discharge ion implantation, the radio frequency discharge frequency is 13.56MHz, the discharge power is 100~200W, and the N2 flow rate is controlled at 0.1~1CC / min; I atom doping element is compound CdI2, and the heating temperature is 180~220℃; by changing the doping conditions of N atoms and I atoms, a series of materials with different N / I concentration ratios are obtained, and the N / I concentration ratio ranges from 1 to 100; Contains iodine (Zn 90% , Cr 10% ) Low temperature annealing treatment of Te:N thin film material, the film temperature is raised to 400℃ and maintained for 10 minutes.
2. The preparation method according to claim 1, characterized in that: Contains iodine (Zn 90% , Cr 10% )The thickness of the Te:N thin film layer is 50~720 nm, and the growth rate is 0.1nm / s.
3. The preparation method according to claim 2, characterized in that: Contains iodine (Zn 90 ,Cr 10% )The thickness of the Te:N thin film layer is 50~360nm.
4. The preparation method according to claim 3, characterized in that: Contains iodine (Zn 90 ,Cr 10% )The thickness of the Te:N thin film layer is 360nm.
5. The preparation method according to claim 1, characterized in that: When the molecular epitaxy technique is used to treat the surface defects of GaAs substrates, the atoms used are Te atoms.
6. The preparation method according to claim 5, characterized in that: The molecular line strength of Te atoms is 5x10 -8 Torr.
7. An iodine-containing rare earth magnetic semiconductor (Zn 90% , Cr 10% )Te:N thin film material, prepared by the preparation method according to any one of claims 1 to 6, characterized in that: The concentration ratio between nitrogen and iodine in the material is 1:1~10:1, and the ferromagnetic Curie temperature of the material is 2K~20K; The hole concentration of the thin film material is 5×10 19 cm -3 ~5×10 20 cm -3 , containing iodine-containing magnetic semiconductors (Zn 90% ,Cr 10% )The resistivity of Te:N thin film material is 0.5Ω•cm~1.5Ω•cm.
8. The film material according to claim 7, characterized in that: The hole concentration of the thin film material is 10 20 cm -3 , containing iodine-containing magnetic semiconductors (Zn 90% ,Cr 10% )The resistivity of Te:N thin film material is 1Ω•cm.
Citation Information
Patent Citations
Highly-doped ZnO:Co magnetic semiconductor film material and preparation method thereof
CN103400679A
Method of preparing room temperature ferromagnetism Zn(1-X)Mn(X)O diluted magnetic semiconductor nano-line
CN1908250A